The Effect of Financial Literacy on Financial Management of Teachers and Employees in Islamic Boarding Schools - Dina Nur Apriani; Kadori; Sutrisno (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2024)
The primary objective of this study is to determine the influence of financial literacy on the financial management practices of teachers and employees at Pon-Pes Nabil Husein in Samarinda. This research employs a quantitative descriptive method, utilizing observation and questionnaires for data collection. The population in this study consists of teachers and employees at Pon-Pes Nabil Husein in Samarinda. A purposive sampling technique was used, selecting 63 samples from a total population of 142 based on specific criteria. The criteria for selection included teachers and employees who are permanent staff and have been employed for at least three years. The results of the study indicate that financial literacy significantly affects financial management. This is evidenced by the t-test results, where t_calculated (7.773) > t_table (2.982) and a significance level of 0.000 < 0.05. Therefore, the null hypothesis (Ho) is rejected, and the alternative hypothesis (Ha) is accepted. This conclusion confirms that financial literacy positively impacts the financial management of teachers and employees at Pon-Pes Nabil Husein in Samarinda. The findings of this study highlight the crucial role that financial literacy plays in enhancing financial management skills among educators and staff.